Dynamics of Business Models in Circular Economy: Shifting Challenges in Pilot Projects - Lauten-Weiss, J.; Friege, H.; Westphal, I.; Brinker, J. (Sustainability & Circularity NOW, 2024)
This study investigates the dynamics of circular business models (CBMs) through a multiple case study of 12 pilot projects funded by the German Federal Ministry of Education and Research between 2019 and 2022. The aim of this study was to draw practical conclusions for CBM pilot projects and public funding tenders, as well as to reveal theoretical insights into the motivation, perceptions of challenges, and potentials regarding CBMs and their shifts over time. Focused on remanufacturing and product-service systems (PSS), the study reveals significant shifts in motivation and perceived challenges before and after the pilot projects. Post-pilot, financial considerations emerged as a primary motivator for CBM adoption, alongside market pull factors and resource availability. However, challenges such as cost-related issues, supply chain complexities, and internal realignment hurdles persisted. Conversely, the perception of market-related challenges had decreased after the pilots, suggesting a growing readiness and adaptability of the market to CBMs. Similarly, experience-related challenges saw a decline, indicating an improvement in knowledge and capabilities within consortia over time. Moreover, the study examines shifts in perceived potential, revealing heterogeneous outcomes across different types of CBMs. While some projects identified new possibilities for value chain cooperation and transparency, others expressed skepticism about further potential, particularly in PSS-focused pilots. This study contributes to the growing body of literature on CBMs by providing empirical insights into the dynamics of circular economy (CE) pilot projects and their impact on organizational learning.
Keywords: Circular business models; Product-as-a-Service; Remanufacturing